Advanced Pre-Clinical Research Approaches and Models to Studying Pediatric Anesthetic Neurotoxicity - Wang, Cheng (Frontiers in Neurology, 2012)
Advances in pediatric and obstetric surgery have resulted in an increase in the duration and complexity of anesthetic procedures. A great deal of concern has recently arisen regarding the safety of anesthesia in infants and children. Because of obvious limitations, it is not possible to thoroughly explore the effects of anesthetic agents on neurons in vivo in human infants or children. However, the availability of some advanced pre-clinical research approaches and models, such as imaging technology both in vitro and in vivo, stem cell and nonhuman primate experimental models, have provided potentially invaluable tools for examining the developmental effects of anesthetic agents. This review discusses the potential application of some sophisticaled research approaches, e.g., calcium imaging, in stem cell-derived in vitro models, especially human embryonic neural stem cells, along with their capacity for proliferation and their potential for differentiation, to dissect relevant mechanisms underlying the etiology of the neurotoxicity associated with developmental exposures to anesthetic agents. Also, this review attempts to discuss several advantages for using the developing rhesus monkey models (in vivo), when combined with dynamic molecular imaging approaches, in addressing critical issues related to the topic of pediatric sedation/anesthesia. These include the relationships between anesthetic-induced neurotoxicity, dose response, time-course and developmental stage at time of exposure (in vivo studies), serving to provide the most expeditious platform toward decreasing the uncertainty in extrapolating pre-clinical data to the human condition.